(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
In this paper I have explored the question "What makes me separate from another person?" by considering it in three different ways: firstly in terms of religion and the supernatural; secondly through the discourse of Martin Heidegger and his notions of thrownness and Dasein; thirdly through the discourse of Particle Physics. Finally I considered what implications the conclusions that I reached from these explorations had for me personally and as a therapist.